2022
DOI: 10.1021/acsomega.2c02067
|View full text |Cite
|
Sign up to set email alerts
|

Tetrafluorophenylene-Containing Vinylbenzyl Ether-Terminated Oligo(2,6-dimethyl-1,4-phenylene ether) with Better Thermal, Dielectric, and Flame-Retardant Properties for Application in High-Frequency Communication

Abstract: In an integrated circuit, signal propagation loss is proportional to the frequency, dissipation factor ( D f ), and square root of dielectric constant ( D k ). The loss becomes obvious as we move to high-frequency communication. Therefore, a polymer having low D k and D f is critical for copper-clad laminates at higher frequencies. For this purpose, a 4-vinylbenzyl eth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…The polymerization reaction of SA9000 is through the free radical mechanism. 21,[38][39][40] It is found that the C C double bonds of SA9000 can be converted into C C single bonds in the presence of a peroxide as initiator. [38][39][40] Therefore, it is expected to create a series of B-f/SA9000 IPN films with good comprehensive properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The polymerization reaction of SA9000 is through the free radical mechanism. 21,[38][39][40] It is found that the C C double bonds of SA9000 can be converted into C C single bonds in the presence of a peroxide as initiator. [38][39][40] Therefore, it is expected to create a series of B-f/SA9000 IPN films with good comprehensive properties.…”
Section: Introductionmentioning
confidence: 99%
“…21,[38][39][40] It is found that the C C double bonds of SA9000 can be converted into C C single bonds in the presence of a peroxide as initiator. [38][39][40] Therefore, it is expected to create a series of B-f/SA9000 IPN films with good comprehensive properties. Meanwhile, the curing temperatures of the prepared IPN prepolymers can be decreased as much as possible.…”
Section: Introductionmentioning
confidence: 99%